2020
DOI: 10.3389/fimmu.2020.01832
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Autoimmune Diabetes of NOD Mice by Immunomodulating Probiotics

Abstract: Type 1 autoimmune diabetes is an autoimmune disease characterized by specific destruction of pancreatic β-cells producing insulin. Recent studies have shown that gut microbiota and immunity are closely linked to systemic immunity, affecting the balance between pro-inflammatory and regulatory immune responses. Altered gut microbiota may be causally related to the development of immune-mediated diseases, and probiotics have been suggested to have modulatory effects on inflammatory diseases and immune disorders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 55 publications
0
15
0
1
Order By: Relevance
“…The microbial community of patients is always influenced by various environmental and clinical factors, such as demography, diet, complications, etc . Therefore, we chose the NOD mice, a model for autoimmune diseases ( Aoki et al., 2005 ; Kim et al., 2020 ), to better evaluate the influence of IL-2 treatment on gut microbiota. The Shannon and equitability indexes in each sample revealed that alpha diversity were changed after low-dose IL-2 therapy ( Supplementary Figure 2A ) .…”
Section: Resultsmentioning
confidence: 99%
“…The microbial community of patients is always influenced by various environmental and clinical factors, such as demography, diet, complications, etc . Therefore, we chose the NOD mice, a model for autoimmune diseases ( Aoki et al., 2005 ; Kim et al., 2020 ), to better evaluate the influence of IL-2 treatment on gut microbiota. The Shannon and equitability indexes in each sample revealed that alpha diversity were changed after low-dose IL-2 therapy ( Supplementary Figure 2A ) .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the beneficial role of different Lactobacillus species on delaying the development of T1D or reducing its complications, using mice models [ 83 , 84 , 85 , 86 ]. In the current study the fecal samples of T1D children showed lower numbers of Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Conditioned media of LA inhibits IL-1β stimulated decrease in occludin and increase in claudin-1 expression and thus preserve intestinal permeability by normalizing the expression of occludin and claudin-1 [89]. Probiotic combination of LA, L. reuteri, L. casei, Streptococcus thermophiles and Bifidobacterium bifidum significantly reduced diabetes incidence and gut permeability [90]. Administration of probiotics LA and Bifidobacterium infantis to the pregnant women daily from embryonic day 15-to 2-week-old postnatally maintained the intestinal integrity of preweaned offspring.…”
Section: La Role In Maintaining Gut Permeabilitymentioning
confidence: 95%